Whole-Cell Based Fluorescence Biosensors for Environmental Applications - W. N., Aisyah; Chai, Mee Kin; Wong, Ling Shing (Institute of Research and Journals (IRAJ), 2015)
Tonnes of wastes from different industries are discarded into the environment yearly, which leads to transfer of organic and inorganic pollutants into various water bodies. The detection of these pollutants profoundly relies on sophisticated equipment such as atomic absorption spectrometer (AAS), and inductively coupled plasma mass spectrometer (ICP-MS). The integration of whole-cells in optical biosensors provides a good sensitivity and accuracy in screening for pollutants in the environment. The inhibition of the metabolic activity by whole cells results in the emission of light such as fluorescence and bioluminescence. This feature is exploited for the development of whole-cell based optical biosensors